HUBUNGAN GAYA HIDUP DENGAN KEJADIAN HIPERTENSI - Andry Sartika; Ferasinta Ferasinta; Panzilion Panzilion (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2023)
As lifestyle changes following the era of globalization, cases of hypertension continue to increase. Hypertension is a condition when the systolic blood pressure is more than 120 mmHg and the diastolic pressure is more than 80 mmHg. This study aims to determine the relationship between lifestyle and the incidence of hypertension. The research design is cross sectional. The population and sample in this study were hypertension sufferers in the working area of ​​the Masmambang Health Center, a total of 135 people were taken by purposive sampling using the proportion estimation formula with a degree of deviation of 10% and a total of 58 samples were obtained. The results of the research on smoking habits obtained a p value <α where the value of p = 0.005 means that there is a significant relationship between smoking habits and the incidence of hypertension. eating habits obtained p value <α where the value of p = 0.005 means there is a significant relationship between eating habits and the incidence of hypertension. Sports habits and physical activity obtained a p value <α where the value of p = 0.000 means that there is a significant relationship between smoking habits and the incidence of hypertension. The habit of drinking coffee has a p value > α where the value of p = 0.673 means that there is no significant relationship between smoking habits and the incidence of hypertension. It is advisable for further research to add other variables such as family economic status and level of knowledge of the disease so that the causes of hypertension in the community can be known more broadly.